The human corticocortical vestibular network - Raiser, T.M.; Flanagin, V.L.; Duering, M.; van Ombergen, A.; Ruehl, R.M.; zu Eulenburg, P. (NeuroImage, 2020)
•Robust modularity of the structural corticocortical vestibular network (CVN).•Similarities in the sensory organization of the CVN between humans and macaques.•Laterality preference in vestibular processing for the right hemisphere.•Structural CVN is characterized by a substantial intrahemispheric connectivity.•Functional CVN is characterized by a strong connectivity for homotopic nodes. Little is known about the cortical organization of human vestibular information processing. Instead of a dedicated primary vestibular cortex, a distributed network of regions across the cortex respond to vestibular input. The aim of this study is to characterize the human corticocortical vestibular network and compare it to established results in non-human primates. We collected high-resolution multi-shell diffusion-weighted (DWI) and state-of-the-art resting-state functional MR images of 29 right-handed normal subjects. Ten cortical vestibular regions per hemisphere were predefined from previous vestibular stimulation studies and applied as regions of interest. Four different structural corticocortical vestibular networks accounting for relevant constraints were investigated. The analyses included the investigation of common network measures and hemispheric differences for functional and structural connectivity patterns alike. In addition, the results of the structural vestibular network were compared to findings previously reported in non-human primates with respect to tracer injections (Guldin and Grusser, 1998). All structural networks independent of the applied constraints showed a recurring subdivision into identical three submodules. The structural human network was characterized by a predominantly intrahemispheric connectivity, whereas the functional pattern highlighted a strong connectivity for all homotopic nodes. A significant laterality preference towards the right hemisphere can be observed throughout the analyses: (1) with larger nodes, (2) stronger connectivity values structurally and functionally, and (3) a higher functional relevance. Similar connectivity patterns to non-human primate data were found in sensory and higher association cortices rather than premotor and motor areas. Our analysis delineated a remarkably stable organization of cortical vestibular connectivity. Differences found between primate species may be attributed to phylogeny as well as methodological differences. With our work we solidified evidence for lateralization within the corticocortical vestibular network. Our results might explain why cortical lesions in humans do not lead to persistent vestibular symptoms. Redundant structural routing throughout the network and a high-degree functional connectivity may buffer the network and reestablish network integrity quickly in case of injury. [Display omitted]